2018
DOI: 10.1016/j.jmb.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of RNA Polymerase I Upstream Activating Factor and the Roles of Histones H3 and H4 in Complex Assembly

Abstract: RNA polymerase I (Pol I) transcription in Saccharomyces cerevisiae requires four separate factors that recruit Pol I to the promoter to form a pre-initiation complex. Upstream Activating Factor (UAF) is one of two multi-subunit complexes that regulate pre-initiation complex formation by binding to the ribosomal DNA promoter and by stimulating recruitment of downstream Pol I factors. UAF is composed of Rrn9, Rrn5, Rrn10, Uaf30, and histones H3 and H4. We developed a recombinant Escherichia coli-based system to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 75 publications
4
13
0
Order By: Relevance
“…Net1-CTR-TAP was expressed in baculovirus infected SF21 cells as recently published 22,[74][75][76] . Specifically, 50 × 10 6 cells were resuspended in buffer F (20 mM HEPES/KOH pH 7.8, 10% glycerol, 200 mM KCl, 1 mM MgCl 2 , 0.2% NP40, 1 mM DTT), lysed by sonication (Branson Sonifier 250 macrotip, cooling in icewater) and cleared by centrifugation (40,000 × g for 40 min at 4°C).…”
Section: Methodsmentioning
confidence: 99%
“…Net1-CTR-TAP was expressed in baculovirus infected SF21 cells as recently published 22,[74][75][76] . Specifically, 50 × 10 6 cells were resuspended in buffer F (20 mM HEPES/KOH pH 7.8, 10% glycerol, 200 mM KCl, 1 mM MgCl 2 , 0.2% NP40, 1 mM DTT), lysed by sonication (Branson Sonifier 250 macrotip, cooling in icewater) and cleared by centrifugation (40,000 × g for 40 min at 4°C).…”
Section: Methodsmentioning
confidence: 99%
“…With hundreds of mutations per strain (Table S2), the total number of mutations screened covered more than one hundred times the size of the S. cerevisiae genome, indicating that the screen had been saturating. Rrn5, Rrn9, and Rrn10 form, together with Uaf30, histones H3 and H4, the UAF for RNA polymerase I (Keener et al, 1997;Keys et al, 1996;Siddiqi et al, 2001;Smith et al, 2018;Tongaonkar et al, 2005). RRN5, RRN9, and RRN10 are essential for cell growth in the fob1D background, while deletion of UAF30 showed only a growth defect (Figures S2A,S2B,and 3C).…”
Section: Rrn5 Rrn9 Rrn10 and Uaf30 Regulate Sir2mentioning
confidence: 99%
“…UAF reconstitution studies of transcriptionally active complex recently revealed new insights into UAF assembly. It was shown that all the UAF-specific subunits interact with histone H3 (23). Interestingly, no single UAF subunit, including the histone subunits, was required for complex integrity, indicating an interconnected network of proteinprotein interaction forms the complex (23).…”
mentioning
confidence: 99%
“…It was shown that all the UAF-specific subunits interact with histone H3 (23). Interestingly, no single UAF subunit, including the histone subunits, was required for complex integrity, indicating an interconnected network of proteinprotein interaction forms the complex (23). Stoichiometry studies also revealed that UAF contains two copies of histone H3 while the remaining subunits are found in single copies, suggesting that UAF contains a novel tetramer-like subcomplex with the Rrn5 histone fold domain (23).…”
mentioning
confidence: 99%